Youtubeurs et politiques : vers une peopolisation numérique ? Focus sur le « concours d’anecdotes » du président Macron - Pierre Camille-Delahaye (Communication)
The 2017 presidential election had the effect of enshrining YouTube as the “new space for political communications”, allowing for a disintermediated, closer-to-the people form of expression. But before being populated by political professionals, YouTube was first the playground of YouTubers, with the most famous among them leveraging their millions of followers to become powerful influencers. It was not long before French politicians entered the YouTube universe and took an interest in these key players in connected society. In late May 2021, a comic YouTube video featuring President Emmanuel Macron caused quite a stir in the French media space. This article looks at what the head of state’s participation in an Internet-exclusive entertainment program can teach us about the staging of politics. The corpus, which includes the famous video, national daily press coverage of the event, and comments posted by Internet users on the digital platform, was subjected to a thematic categorical-content analysis that allowed us to categorize statements inductively. The event appears to be representative of the current changes in political communication in France and their impact on the French public space.